Accuracy evaluation of Roche and Siemens tacrolimus and cyclosporine assays in comparison with liquid chromatography-tandem mass spectrometry. (18th August 2018) - Ko, Dae-Hyun; Cho, Eun-Jung; Lee, Woochang; Chun, Sail; Min, Won-Ki
Abstract: Therapeutic drug monitoring of tacrolimus and cyclosporine is crucial to the success of organ transplantation. We evaluated the analytical performances and accuracy of two commercially available tacrolimus and cyclosporine assays (Roche ISD and Siemens) in comparison with liquid chromatography-tandem mass spectrometry (LC-MS/MS). A total of 342 leftover whole blood samples requested for tacrolimus or cyclosporine assays were stored at −20 °C until analysis. Repeatability and between-run imprecision were evaluated using quality control materials provided by the manufacturer. Ring trial samples were used for the assessment of recovery. The results of the Roche ISD assay were compared with those of Siemens tacrolimus and cyclosporine assays and LC-MS/MS. Repeatability and between-run imprecision were 2.1–5.3% and 2.6–7.5%, respectively. Recovery of Roche ISD was 85.7 − 90.6% for cyclosporine and 96.2–98.5% for tacrolimus. The two immunoassays showed slight positive biases relative to LC-MS/MS for cyclosporine. For tacrolimus, Roche ISD produced virtually identical results to those of LC-MS/MS, whereas Siemens showed proportional differences, especially in patients receiving kidney transplantation. The analytical performances of Roche ISD were generally acceptable, especially regarding accuracy. Clinical laboratory staff should be aware of the strengths and weaknesses of commercial immunoassays in order to ensure accurate results.